(3GdJLfjS aj GdMSGHs - (3eMeO Hf eMeO Hf YHO GdQTjO GdSLGhfOj GdMfaj, SQGL GdOjf CHh WGgQ,J (B598 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hGdYGbHI ddeJbjf ai GdJLfjS eYfi GdJLfjS Cf JLYd GdcSQ aUGYOG ef LfS hGMO s
(3BNQgG (B:s
(3hGdMeO ddg hMOg hUdi Gdgd Ydi SjOfG eMeO hSde s
(3Vef eLehY , JQJjHgG (B: 2s
(3GdfSNI ebGHdI ceG ai BNQgGs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B233 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B6 - (3U (B106s
Keywords: (3GdQjGVjGJs